2006
DOI: 10.1007/s10803-006-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Rules versus Prototype Matching: Strategies of Perception of Emotional Facial Expressions in the Autism Spectrum

Abstract: When perceiving emotional facial expressions, people with autistic spectrum disorders (ASD) appear to focus on individual facial features rather than configurations. This paper tests whether individuals with ASD use these features in a rule-based strategy of emotional perception, rather than a typical, template-based strategy by considering outcome implications of these strategies. Rule-based strategies are more tolerant of extreme stimuli than are template-based ones. Tolerance for exaggerated emotional facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 54 publications
10
91
0
2
Order By: Relevance
“…In contrast, a control group was less likely to accept exaggerated facial expressions as good examples, preferring the average facial expressions. This pattern in the control group is consistent with a template matching strategy, according to these authors (Rutherford and McIntosh 2007). In addition, recent research suggests that sub-groups of individuals with autism can be defined based on performance on faceprocessing tasks ).…”
Section: Face Processing In Autism Spectrum Disorderssupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, a control group was less likely to accept exaggerated facial expressions as good examples, preferring the average facial expressions. This pattern in the control group is consistent with a template matching strategy, according to these authors (Rutherford and McIntosh 2007). In addition, recent research suggests that sub-groups of individuals with autism can be defined based on performance on faceprocessing tasks ).…”
Section: Face Processing In Autism Spectrum Disorderssupporting
confidence: 86%
“…Some studies report deficits in all types of face processing (Gepner et al 1996), in face recognition (Boucher and Lewis 1992;Braverman et al 1989;Klin et al 1999;Tantam et al 1989;de Gelder et al 1991) and the identification of emotional facial expressions (Pelphrey et al 2002;Celani et al 1999;Hobson et al 1988;Hobson 1986) while others have not found the expected differences in face discrimination (Nishimura et al 2007; or emotion perception (Loveland et al 1997;Ozonoff et al 1990;Buitelaar et al 1999). Other research has focused on processing strategies and has found evidence that those with autism use different strategies when identifying emotional facial expressions (Rutherford and McIntosh 2007;de Gelder 2001, 2003). Specifically, Rutherford and McIntosh found that people with ASD were more tolerant of exaggeration in facial expression, consistent with the idea that they might be using a rule-based emotion perception strategy.…”
Section: Face Processing In Autism Spectrum Disordersmentioning
confidence: 99%
“…Instructions would need to be adjusted, however, so that children focused on the character's emotions rather than their own feelings. The ability to identify others' feelings is often compromised in children on the autistic spectrum [47,48]. Similarly, applications in educational settings for children with impaired emotion recognition due to learning disabilities could be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for the girls with ASD, expressions of happiness and anger were more difficult to recognize from the eyes compared to the control girls even the girls with ASD were significantly older than the control girls. These findings may be due to the fact that individuals with autism need more exaggerated facial gestures to be able to interpret the emotional state of others (Rutherford and McIntosh 2007) correctly, or that they need more cues, such as verbal or environmental contents, to decode the emotion correctly (Grossman et al 2002;Lindner and RosĂ©n 2006).…”
Section: Discussionmentioning
confidence: 99%